APPROACHES TO THE LEADERSHIP IN EDUCATION - Rutkiene, Ausra; Tandzegolskiene, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The concept of leadership in education has been influenced by several disciplines: sociology, psychology, political science, economics, philosophy (Simkins, 2005, English, 2006). The development of the concept of leadership has also been greatly influenced by the analysis of organizational systems from a sociological perspective (English, 2006).The analysis of scientific literature shows that the concept of leadership in education is analyzed and presented by many authors from different points of view. Leadership in education is analyzed by emphasizing the position of administration and management, reviewing changes in the school system and leadership models that help to implement systemic changes in school, focusing on the learning process and curriculum development, emphasizing leadership in higher education, narrative, historical context, and meta-analysis.The results of the focus group with higher education staff show that leadership in higher education covers a wide range of activities: administration, management, teaching, research, supervision of final theses, decision-making in projects - basically sociological, political, administrative, philosophical aspects of leadership are incorporated.